Transumanesimo e progresso morale - Di Ceglie, Roberto (Filosofia Morale/Moral Philosophy, 2024)
In this article, it is argued that it is highly unlikely that the technological progress promoted by transhumanists can generate the moral progress (moral enhancement) they preach. After examining the meaning and value of the link between technological progress and moral progress, three basic limits to the possibility of moral enhancement are discussed. These are “technological ignorance”, “technological passivity”, and “technological easiness”. Finally, it will be noted that they can be exacerbated given that the unknown is a typically transhumanist feature of the future horizon of technology.